Lack of Genetic Structure Among Populations of Striped Flea Beetle Phyllotreta striolata (Coleoptera: Chrysomelidae) Across Southern China - Li, Qian; Li, Guang-Mei; Zheng, Yong-Li; Wei, Shu-Jun (Frontiers in Ecology and Evolution, 2022)
The striped flea beetle (SFB) Phyllotreta striolata (Fabricius) (Coleoptera: Chrysomelidae) is a major pest of cruciferous vegetables in southern China. The population diversity and genetic structure of SFB are unknown. Here, we assembled a draft genome for the SFB and characterized the distribution of microsatellites. Then, we developed 12 novel microsatellite markers across the genome. We used a segment of the cox1 gene sequence and newly developed microsatellite markers to genotype the genetic diversity of SFB across southern China. There were 44 mitochondrial haplotypes in the SFB populations, with haplotype #2 as the most widespread. The population genetic differentiation was very low, indicated by FST values (<0.05 except for Guangxi population with other populations based on mtDNA), high gene flow (4.10 and 44.88 of mtDNA and microsatellite respectively) and Principal Coordinate Analysis across all populations. Mantel test showed genetic distance in SFB was significantly associated with geographic distance based on microsatellites (R2=0.2373, P=0.014) while result based on mtDNA (R2=0.0365, P=0.155) showed no significant difference. The phylogenetic analysis did not find any geographically related clades among all haplotypes. Analyses based on microsatellites showed a lack of population genetic structure among all populations. Our study provides a foundation or the future understanding of the ecology and evolution of SFB and its management.